ปัจจัยทางจิตสังคมที่เกี่ยวข้องกับพฤติกรรมการบริการเชิงรุกของพนักงานดีแทค - เพลาวรรณ์(Chaninya Paerawan), ชนินญา; กิจธรธรรม(Wichuda Kijtorntham), วิชุดา (Journal of Behavioral Science for Development, 2016)
(Psycho-Social Factors Relating to Proactive Service Work Behaviors of Customer Service of Total Access Communication PCL) Abstract The purposes of this research 3 reasons 1) to study the interaction between a psychological and social characteristics that affect performance, proactive services of DTAC overall and groups with biological, social differences. 2) to compare the operational behaviors proactive services with variable characteristics, mental and social aspects of DTAC overall and groups with Organic different social and 3) to describe and predict the behavior of service performance proactively. With variable characteristics, mental and social aspects of employee DTAC. The samples Staff in the Office Customer Service Company Battle Action Set Communications Limited (PLC), or DTAC, who perform customer service as Office, customers of the 26 branches, 300 employees were selected using the proportional sample of the population. The results showed that: 1) employee future orientation - under their control if it has the support of minority organizations. There will be those who Behavior services rather than proactive staff with the support of the organization 2) Employee future orientation - self control, if it is backed by high-tech enterprise will be those who have a habit of working outreach least three. ), a backrest that characterizes the self control and broadcast little social workers DTAC has undergone a jobs Deputy 4) employees with a future orientation control their elevated in female age. Working 10 years in the Jobs Retention 5) Employees with the support of the organization's high prevalence of working age 5-10 Year Degree Master Position Device Service and jobs Deputy 6) employees. loyalty to the organization and is broadcast on society. Found the staff working age 5-10 years, and the employees are very loyal to the organization and to convey low social as found in the staff working age up to 10 years 7) staff is broadcast on society in the group. Jobs Device Service Jobs Deputy. his research aims three reasons: Keywords: the behavior of service performance proactively